Análisis del procedimiento de revalorización de activos fijos del gobierno autónomo descentralizado del cantón Chone - Molina Santana, Ángel Alexy (2022)
This investigation sought to analyze the fixed asset revaluation procedure of the Decentralized Autonomous Government in Chone canton. A qualitative, analytical methodology was used, in addition to field research that allowed the study of the revaluation process, comparing it with the International Public Sector Accounting Standards and the respective instructions of the Ministry of Finance. The results of the physical verification of assets determined that they were revalued at the current market value, which allowed to affirm that the accounting balance of movable property increased and real estate had a decrease, this did not cause the final equity to increase substantially and therefore, it did not affect the financial statements of the institution. It is concluded that it is important that the institution carry out the process as indicated in the Regulation of Administration and Control of Public Sector Assets every three years, at least and five at most.